Imaging and Treatment of Post–90Y Radioembolization Radiation Dermatitis. (March 2019) - Huang, Hian Liang; Venkatanarasimha, Nanda; Chan, Chung Yip
Abstract : Abstract: 90 Y microspheres have been widely used for treatment of liver-dominant malignancies. There have been a few case reports of radiation dermatitis post–inadvertent falciform artery 90 Y radioembolization and a few retrospective studies with prophylactic coiling or use of ice packs prior to radioembolization. Our patient had inadvertent falciform artery radioembolization, which was not predicted on pretherapy angiography or 99m Tc–macroaggregated albumin SPECT/CT but was localized on posttherapy 90 Y PET/CT and treated with topical betamethasone valerate 0.1% BD and ice packing immediately postprocedure. He subsequently developed a small area of periumbilical radiation dermatitis, which resolved after 4 weeks.